2001
DOI: 10.1097/00000539-200108000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Epidural Bupivacaine Attenuates Supraventricular Tachyarrhythmias After Pulmonary Resection

Abstract: We examined whether postoperative thoracic sympathetic blockade by thoracic epidural bupivacaine after pulmonary resection might reduce the tachyarrhythmias that may result from the relative sympathotonic status produced by injury to the cardiac parasympathetic nerves. The continuous infusion of thoracic epidural bupivacaine was shown to reduce supraventricular tachyarrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
1
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 19 publications
0
22
1
2
Order By: Relevance
“…A meta-analysis of patients undergoing various surgeries has confirmed this potential and shows that epidural analgesia reduces post-operative myocardial infarctions by 40%; thoracic epidural analgesia is superior to lumbar epidural analgesia in this respect [200]. There is some evidence that thoracic epidural local anaesthetics reduce the incidence of supraventricular arrhythmias [201], which occur in 20-30% of post-thoracotomy patients [202,203] and are associated with an increased mortality [204,205].…”
Section: Epidural Solutionsmentioning
confidence: 99%
“…A meta-analysis of patients undergoing various surgeries has confirmed this potential and shows that epidural analgesia reduces post-operative myocardial infarctions by 40%; thoracic epidural analgesia is superior to lumbar epidural analgesia in this respect [200]. There is some evidence that thoracic epidural local anaesthetics reduce the incidence of supraventricular arrhythmias [201], which occur in 20-30% of post-thoracotomy patients [202,203] and are associated with an increased mortality [204,205].…”
Section: Epidural Solutionsmentioning
confidence: 99%
“…During cardiothoracic surgery, mechanical manipulation of heart and pericardium leads to a local tissue trauma and local inflammatory response which may both lead to POAF [31][32][33]. Heart manipulation may be responsible also for a direct and local imbalance between sympathetic and parasympathetic tone, (see Figure 1).…”
Section: Mechanical Factors Pain and Sympathetic Stimulationmentioning
confidence: 99%
“…16 A subsequent prospective randomized study demonstrated reduced incidence of arrhythmias in patients with epidural analgesia following pulmonary resection in lung cancer patients. 17 However, that study was not limited to thoracoscopy.…”
mentioning
confidence: 99%
“…16 Une étude randomisée prospective subséquente a démontré une incidence réduite d'arythmies chez les patients bénéficiant d'une analgésie péridurale après une résection pulmonaire chez les patients atteints de cancer du poumon. 17 Cette étude ne se limitait cependant pas à la thoracoscopie.…”
unclassified